Islam, Oil and Geopolitics: By Elizabeth van Wie Davis and Rouben Azizian, eds. (Lanham, Maryland: Rowman & Littlefield, 2007. 288 pages) (American Journal of Islam and Society, 2009)
Emerging from the heap of the Soviet empire into a backwater landmass,the CentralAsian republics of Kazakhstan, Kyrgystan, Tajikistan, Turkmenistan,and Uzbekistan have been increasingly gaining in significance andimportance as the rumblings of a new Great Game is being sounded on theirterritory.According to this book, the three great powers – the United States,Russia, and China – are expected to play determinate roles in the politics and shaping of this region’s evolution on the world stage. The role of thesenewly independent republics, however, is less clear or easy to forecast,however, for they seem to be still in the process of forging their nationalidentities and deciding upon the thrust of their global relations, alliances,and interests.In addition, whether they will continue to be able to maintain theirnewly gained independence, particularly given their vulnerability as landlockedcountries, remains a significant question. Russia, their earlier master,is seeking to reassert its position in what it considers to be its natural sphereof influence. The rising neighboring Chinese giant is developing both economicand strategic interests beyond its borders and into that region. TheAmerican superpower is intruding as a major player into both countries’backyard under the pretext of fighting terrorism and spreading freedom anddemocracy (p. 2). The outcome of the interplay of sometimes traversing yetfrequently conflicting geopolitical as well as economic interests is what thisbook seeks to explore. Fusing the explosive elements of geopolitics, religion,and energy, this four-part book brings together twenty internationalpolicy and security analysts in a conversation about the meaning, from differentperspectives, of a post-9/11 world to the United States and its allies(actual or potential), Russia, and China, as well as to regional powers andthe CentralAsian republics ...